Admission Systolic Blood Pressure Predicts the Number of Blood Pressure Medications at Discharge in Patients With Primary Intracerebral Hemorrhage. Issue 2 (March 2018) - Khawaja, Ayaz M.; Shiue, Harn; Boehme, Amelia K.; Albright, Karen C.; Venkatraman, Anand; Kumar, Gyanendra; Lyerly, Michael J.; Hays-Shapshak, Angela; Mirza, Maira; Gropen, Toby I.; Harrigan, Mark R.
Abstract : Background: Control of systolic blood pressure (SBP) after primary intracerebral hemorrhage improves outcomes. Factors determining the number of blood pressure medications (BPM) required for goal SBP<160 mm Hg at discharge are unknown. We hypothesized that higher admission-SBPs require a greater number of BPM for goal discharge-SBP<160 mm Hg, and investigated factors influencing this goal. Materials and Methods: We conducted a retrospective review of 288 patients who presented with primary intracerebral hemorrhage. Admission-SBP was obtained. Primary outcome was the number of BPM at discharge. Comparison was made between patients presenting with and without a history of hypertension, and patients discharged on <3 and ≥3 BPM. Results: Patients with hypertension history had a higher median admission-SBP compared with those without (180 vs. 157 mm Hg, P =0.0001). In total, 133 of 288 (46.2%) patients were discharged on <3 BPM; 155/288 (53.8%) were discharged on ≥3 BPM. Hypertension history ( P <0.0001) and admission-SBP ( P <0.0001) predicted the number of BPM at discharge. In patients without hypertension history, every 10 mm Hg increase in SBP resulted in an absolute increase of 0.5 BPM at discharge ( P =0.0011), whereas in those with hypertension, the absolute increase was 1.3 BPM ( P =0.0012). In comparison with patients discharged on <3 BPM, patients discharged on ≥3 BPM were more likely to have a higher median admission-SBP, be younger in age, belong to the African-American race, have a history of diabetes, have higher median admission–National Institutes of Health Stroke Scale and modified Rankin Scale of 4 to 5 at discharge. Conclusions: An understanding of the factors influencing BPM at discharge may help clinicians better optimize blood pressure control both before and after discharge.